Spatial Analysis of the Labour Market by Using Econometric Tools. The Case of Lower Silesia Region (Dolnosĺaskie voivodship); Przestrzenna analiza rynku pracy przy uzẏciu narzedzi ekonometrycznych. Przykład wojewod́ztwa dolnosĺaskiego - Elzḃieta Litwinśka (Comparative Economic Research. Central and Eastern Europe, 2012)
This paper presents the application of econometric techniques to examine the labour market in Lower Silesia. First the analysis was performed on a data set for variables connected with labour market recorded in poviats (NUTS 4). In order to determine the existence of spatial autocorrelation Moran's statistics I was calculated. Then the spatial regression model was used to describe the relationship between the rate of unemployment and other variables. Next, LISA cluster maps were generated for units at NUTS 5 level. The results indicate the spatial dimension of the unemployment and its tendency to creating concentrations. – – Artykuł prezentuje wykorzystanie technik ekonometrycznych do badania rynku pracy na Dolnym Sĺasku. Najpierw analiza dotyczyła zbioru danych zwiazanych z rynkiem pracy na poziomie powiatoẃ (NUTS 4). W celu zbadania istnienia autokorelacji przestrzennej policzono statystyke Morana I, potem został uzẏty model regresji przestrzennej do opisu zalezṅosći pomiedzy stopa bezrobocia a innymi zmiennymi. W nastepnym kroku wygenerowano mapy obrazujace lokalny wskazńik zalezṅosći przestrzennej LISA dla gmin (NUTS5). Wyniki wskazuja na przestrzenny wymiar bezrobocia i jego tendencje do tworzenia koncentracji.
Keywords: 330